EFEKTIVITAS PEMILIHAN UMUM: PERBANDINGAN LEMBAGA PEMILIHAN UMUM REPUBLIK FEDERATIF BRASIL DAN REPUBLIK INDONESIA - Immanuel, Glenn Kevin; Erawan, I Ketut Putra; Puspitasari, Ni Wayan Radita Novi (Jurnal Nawala Politika, 2023)
One of the pillars and prerequisites in a country that adheres to a democratic system such as Indinesia and Brazil is general election. In organizing general election, the role and fuction of the general election institution is very important, considering that  electoral governance lies with the election administrator. This study tries to see how fuctions and roles of electoral institution in Indonesia and Brazil. This studies use most different system design political comparison method. There are many differences in the roles and function of electoral institution between Indonesia and Brazil, even though the electoral institution in these two countries both have an independent nature.